If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-49f=-3
We move all terms to the left:
-49f-(-3)=0
We add all the numbers together, and all the variables
-49f+3=0
We move all terms containing f to the left, all other terms to the right
-49f=-3
f=-3/-49
f=3/49
| 3g-13=91 | | x+14/5=27 | | -5/6d=20 | | 4x-8+3x-5+92+91+125=540 | | 87=u/7+49 | | |-5/6d|=20 | | 17-4d=1 | | d/6-25=32 | | 4u-10=2(u+1) | | x+5x+8=26-3x, | | 9z=10z+9 | | x4−1=3 | | n/9-81=-74 | | Y^2+2y-24y=0 | | 6(y+7)=4y+26 | | 8+h/10=1 | | 6-12x=x+45 | | -7y+8=-5(y-4) | | 38+2y=4y-24 | | 15+j=45 | | 7y-5=540/4 | | 6=t+4 | | -x/8=56 | | 5x^2-2=-76 | | -x/8=-56 | | 4(-1-7m)=-8m+36 | | 20x^2=500 | | -8-6n=-4(2+n) | | 3(v+4)=-8v-10 | | -7x-8(1+x)=4x-19 | | -7(7a-5)=35-8a | | 3=r/3+2 |